Production and Purification of Mannan-Degrading Enzymes from Palm Kernel Cake Fermented by Aspergillus Niger and Sclerotium Rolfsii - Ab. Razak, Nor asma (2006)
Mannan-degrading enzymes are alpha-galactosidase (E.C 3.2.1.22, α-GAL), 1,4-beta-D-mannanase (E.C. 3.2.1.78, MANN) and beta-mannosidase (E.C 3.2.1.25, β-MANN). Mannan-degrading enzymes have been used quite extensively in animal compound feed, beverage and fruit-juices industries, food processing, paper industry and therapeutic field. The submerged fermentation is a process whereby microbes of interest will grow, and utilize the moisted substrate material in the presence of free water. Palm kernel cake (PKC) has been used in diets for both non-ruminants and ruminants. The objectives of this study were in the confirmation selection and quantification, production and profiling of mannan-degrading enzymes from local fungial isolates as well as in concentrated and partially partial ly purification of the mannan-degrading enzymes from submerged fermentation and saccharification of PKC using enzymes obtained from fermentation A. niger by 2-level design approach In this study, staining of locally isolated fungi using carbonyl fuchsin and methylene blue, and decolouration of different modified carbon-limited media were conducted to confirm the types of strains and their ability to produce mannan-degrading enzymes. Results showed that A. niger and S. rolfsii can produce mannan-degrading enzymes. The fungi were grown in submerged fermentation of PKC to produce mannan-degrading enzymes.. The highest alpha-galactosidase was obtained on day 13 of fermentation (0.128 + 0.004 U/ml) when using A. niger and on day 18 (0.126 + 0.003 U/ml) when using S. rolfsii. Analysis also showed that enzyme activities for beta-mannanase using S. rolfsii were the highest at day 17 (3.166 + 0.033 U/ml) and for A. niger (2.482 + 0.108 U/ml) at day 8. Meanwhile the highest beta-mannosidase were obtained at day 16 for A. niger (0.128 + 0.002 U/ml) and for S. rolfsii day 16 (0.116 + 0.006 U/ml). Profile activities of alpha-galactosidase were 0.128 + 0.004 U/ml and 0.126 + 0.003 U/ml using A. niger and S.rolfsii. Analysis also showed that profile enzyme activities for beta-mannanase using S. rolfsii was 3.166 + 3.368 U/ml and for A. niger, 2.482 + 1.089 U/ml. Meanwhile profile activities of betamannosidase were 0.128 + 0.002 U/ml and 0.116 + 0.006 U/ml for A.niger and S. rolfsii. Precipitation of acetone and ammonium sulphate at -20°C and 0°C was done to concentrate partially purify the enzymes. Results showed that 100 % ammonium sulphate saturation at 0°C precipitated high activities of alpha-galactosidase from A. niger and S. rolfsii , and also beta-mannosidase from S. rolfsii while 80 % ammonium sulphate saturation, respectively at 0°C precipitated beta-mannosidase from A. niger. Meanwhile, high beta-mannanase from A. niger and S. rolfsii was obtained when precipitate using 80 % and 90 % ammonium sulphate saturation at 0°C saturation. In order to concentrate and partially purified purify the enzyme, conventional purification procedures undertaken were selection of precipitation using acetone and ammonium sulphate procedures and , gel filtration chromatography and molecular weight estimation. The results showed that high activities of alpha-galactosidase and beta-mannosidase from A. niger and S. rolfsii can be obtained using acetone at -20°C. Enzymes beta-mannanase from A. niger, beta-mannanase and beta-mannosidase from S. rolfsii precipitated at 80 %, 90 % and 100 % saturation using ammonium sulphate saturation at 0°C. Gel filtration chromatography successfully in partially purified purifiedconcentrated alphagalactosidase and beta-mannosidase from A. niger at 5.709 U/ml and 2.324 U/ml specific activities with 2191 and 780 fold, but beta-mannanase were not successfully concentratedpurified. Meanwhile alpha-galactosidase, betamannosidase and beta-mannanase from S. rolfsii were purified at 0.162 U/ml, 4.69 U/ml and 0.003 U/ml specific activities with 380, 177 and 3 fold. The molecular weight Aacetone and ammonium sulphate precipitated alpha-galactosidase from A. niger were estimated to be between 10 kDa, 30 kDa and 35 - 225 kDa and 30 kDa and 35 - 100 kDa using sodium dodecyl sulphate-polyacrylamide gel (SDS-PAGE). Molecular massweight for beta-mannanase from A.niger using acetone precipitateion were between 100 kDa and 150 kDa; beta-mannanase from S. rolfsii precipitateion using acetone and ammonium sulphate were between 35 kDa and 30 - 100 kDa. The beta-mannosidase from A. niger precipitatte ion using acetone and ammonium sulphate awere between 100 kDa and 150 kDa. However, Meanwhile, molecular massweight for alpha-galactosidase and beta-mannosidase from S. rolfsii precipitated both using acetone and ammonium sulphate precipitation, and beta-mannanase from A. niger using ammonium sulphate precipitation wcould not be detected. Screening for several parameters that influenced the production of reducing sugars from PKC using crude and partially purifiedconcentrated enzymes from A. niger were also carried out. The selected parameters were effects of incubation days (1, 2 and 3), incubation temperatures (30, 40 and 50°C), initial pH (3, 4 and 5), substrate concentration (2, 5 and 7 %), autoclaved or not autoclaved, and enzymes volume relationship (1, 2 and 3 ml). The results showed saccharification using concentrated partial purified beta-mannanase on day 8 gaives the highest reducing sugar of about 41.90 mg/ml with 60 % efficiency yield. compared to alpha-galactosidase and beta-mannosidase. The parameters used to obtain highest reducing sugars were autoclaved substrate, substrate concentration %, incubation temperature 50°C, incubation time 3 days, crude enzymes 3 ml and initial pH 3.